2019
DOI: 10.3390/life9020042
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of a Prototypical Autocatalytic Reaction Network

Abstract: Network autocatalysis, which is autocatalysis whereby a catalyst is not directly produced in a catalytic cycle, is likely to be more common in chemistry than direct autocatalysis is. Nevertheless, the kinetics of autocatalytic networks often does not exactly follow simple quadratic or cubic rate laws and largely depends on the structure of the network. In this article, we analyzed one of the simplest and most chemically plausible autocatalytic networks where a catalytic cycle is coupled to an ancillary reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Often, the autocatalytic network does not involve a series of catalysts – only one catalyst and a series of non‐catalytic intermediates (Figure 3c). Semenov and Skorb showed that thioester autocatalysis, [22] some variants of azide‐alkyne autocatalysis [23] and the formaldehyde sulfide reaction [24] all belong to this type of network structure [25] . This network always results in exponential growth after some lag phase where growth is slower than an exponential rate.…”
Section: Kinetics Of Autocatalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Often, the autocatalytic network does not involve a series of catalysts – only one catalyst and a series of non‐catalytic intermediates (Figure 3c). Semenov and Skorb showed that thioester autocatalysis, [22] some variants of azide‐alkyne autocatalysis [23] and the formaldehyde sulfide reaction [24] all belong to this type of network structure [25] . This network always results in exponential growth after some lag phase where growth is slower than an exponential rate.…”
Section: Kinetics Of Autocatalysismentioning
confidence: 99%
“…The contribution of the direct reaction to the overall production of products is an important characteristic of a particular autocatalytic reaction. If the contribution of the direct reaction is too strong, the dynamic effects of autocatalysis will be masked; the system properties emerging from autocatalysis such as Darwinian selection, [25] bistability, propagation of the reaction front, and oscillations will not appear [11a] . Let's consider the simplest example of an autocatalytic reaction: trueS+Ak12A4pt …”
Section: Kinetics Of Autocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rapid development of computer technologies, more attention is paid to the areas of their intersection with chemistry, including infochemistry [ 1 , 2 , 3 , 4 ]. In order to prepare the 21st century students to be successful researchers and engineers in emerging fields of chemistry, informatics and programming, it is necessary to provide more educational tools to ensure deeper understanding of the fundamental principles in the aforementioned areas.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid development of computer technologies, more attention is paid to the areas of their intersection with chemistry, including infochemistry [1][2][3][4]. In order to prepare the 21st century students to be successful researchers and engineers in emerging fields of chemistry, informatics and programming, it is necessary to provide more educational tools to ensure deeper understanding of the fundamental principles in the aforementioned areas.…”
Section: Introductionmentioning
confidence: 99%